Delayed diagnosis of congenital hypothyroidism in an adolescent results in avoidable complications: a case report - Indra Ihsan; Eka Agustia Rini (Paediatrica Indonesiana, 2017)
Delayed diagnosis of congenital hyporhyroidism (CH) remains a serious problem. A retrospective analysis of 1,000 CH cases in Turkey found a mean age of 49 months at the time of clinical diagnosis. Only 3.1% of cases were diagnosed during the neonatal period and 55.4% were diagnosed after 2 years of age.1 In Cipto Mangunkusumo Hospital, Jakarta, 53% cases were diagnosed at 1-5 years, 3.3% at 6-12 years, and 6.7% after 12 years of age, while the remainder were diagnosed at < 1 year of age.2 The majority of affected children exhibit signs and symptoms that are highly non-specific, as most infants with CH are asymptomatic at birth, and only 5% of cases can be diagnosed based on clinical examination during the first day of life.3 The other factors that contribute to delayed diagnosis are uneducated parents, who do not notice or dismiss the importance of mild/moderate deviations in physical and mental growth, as well as constipation, feeding difficulties, or other vague, non-specific symptoms in infancy. Parents are often unaware of the importance of early diagnosis and commencement of therapy for CH.4